PERTIMBANGAN PARTAI POLITIK DALAM PENENTUAN CALON KEPALA DAERAH (STUDI : PARTAI DEMOKRASI INDONESIA PERJUANGAN PADA PILKADA 2020) - Widia Putra, Ida Bagus Wahyu; Noak, Piers Andreas; Apriani, Kadek Dwita (Jurnal Nawala Politika, 2022)
This study aims to determine the considerations of political parties in determining candidates for regional heads in the 2020 simultaneous elections. The Rational Choice Theory by Barbara Geddes is used as an analytical knife to dissect the considerations of the PDI-P in selecting candidates for regional heads and deputy regional heads in the 2020 simultaneous elections. the dominant party theory put forward by Giovanni Sartori is also used as an analytical knife to dissect the existence of Party Domination carried out by PDI-P with a regional basis strategy. By using qualitative methods through interviews, the results of the research are as follows: the election of Kadek Agus Arya Wibawa as a Candidate for Deputy Mayor cannot be separated from regional factors, where the Candidate for Mayor comes from the East Denpasar District and the Deputy Mayor Candidate comes from the South Denpasar District. The unification of votes from these two sub-districts formed the dominant party in Denpasar. Apart from that, Kadek Agus' enormous mass support certainly gave PDI-P its own advantages, both in terms of existence and increasing party mass.